Evaluation of Cytotoxicity and Antifertility Effect of Artemisia kopetdaghensis - Davood Oliaee; Mohammad Taher Boroushaki; Naiime Oliaee; Ahmad Ghorbani (Advances in Pharmacological Sciences)
To date, there is no report on safety of Artemisia Kopetdaghensis. This study aimed to determine the possible undesirable effects of A. Kopetdaghensis on reproduction of female rats. The pregnant rats were treated (i.p.) with vehicle or 200 and 400 mg/kg of A. Kopetdaghensis hydroalcoholic extract from the 2nd to 8th day of pregnancy. Then, number and weight of neonates, duration of pregnancy, and percent of dead fetuses were determined. Also, cytotoxicity of this plant was tested using fibroblast (L929) and ovary (Cho) cell lines. The A. Kopetdaghensis had no significant effect on duration of pregnancy, average number of neonates, and weight of neonates. However, administration of 200 and 400 mg/kg of the extract led to 30 and 44% abortion in animals, respectively. The extract at concentrations ≥200 μg/mL significantly (P<0.001) inhibited the proliferation of L929 fibroblast cells. Regarding the Cho cells, the extract induced toxicity only at concentration of 800 μg/mL (P<0.01). Our results showed that continuous consumption of A. Kopetdaghensis in pregnancy may increase the risk of abortion and also may have toxic effect on some cells.